Alcoholism and coagulating gland: Androgen and insulin like growth factor-1 receptor features - Montico, Fabio; Favaro, Wagner Jose; Candido, Eduardo Marcelo; Martinez, Marcelo; Felipe Pinheiro, Patricia Fernanda [UNESP]; Martinez, Francisco Eduardo [UNESP]; Alves Cagnon, Valeria Helena (Churchill Livingstone, 2010)
The aim of this work was to characterize the structural and molecular changes in the coagulating gland from rats submitted to long-term alcohol treatment, as well as the possibility of recovery of these parameters after interrupting the alcohol administration. Ten Wistar and twenty UChB rats were divided into: Control group received tap water; Alcoholic group received 10% (v/v) ethanol daily for 150 days; and Abstinent group, received 10% (v/v) ethanol daily for 120 days and then tap water like the control for another 30 days. After 150 days, samples from the coagulating glands were processed for morphological and immunohistochemical analyses. The results showed atrophied epithelium and hypertrophied stroma, especially in the alcoholic group. Intensed androgen receptor (AR) immunolocalization was verified in the epithelium and weak in the stroma of the control group in relation to the other groups. Intensed insulin-like growth factor receptor-1 (IGFR-1) immunolocalization was verified in the stroma of the alcoholic and abstinent groups. Thus, it could be concluded that the excessive alcohol consumption caused morphological and molecular changes in the coagulating gland, characterizing the inverse relation of AR and IGFR-1 localization. The alcohol was an important factor in cellular mitosis occurrence, which could be fundamental element involved in glandular lesions. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Alcoholism; Coagulating gland; UChB rat; Morphology; Immunohistochemistry